Some Indices over a New Algebraic Graph - Nurten Urlu Özalan (Journal of Mathematics)
In this paper, we first introduce a new graph ΓN over an extension N of semigroups and after that we study and characterize the spectral properties such as the diameter, girth, maximum and minimum degrees, domination number, chromatic number, clique number, degree sequence, irregularity index, and also perfectness for ΓN. Moreover, we state and prove some important known Zagreb indices on this new graph.